2014
DOI: 10.1186/s12888-014-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

Community outreach for patients who have difficulties in maintaining contact with mental health services: longitudinal retrospective study of the Japanese outreach model project

Abstract: BackgroundJapan still has the highest ratio of beds devoted to psychiatric patients in the world. In 2011, in order to reduce re-hospitalization of patients who became disconnected from regular contact with outpatient medical services, the Japanese Ministry established the Japanese Outreach Model Project (JOMP). In this study, we will explicate the JOMP project protocol and investigate the rate and length of hospital admission, impairments of social function and problematic behavior at the follow-up period (6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…Our findings support a previous study which showed that PHNs utilized multiple sources of data for identifying an individual's health condition 18) . Additionally, in Japan, many families live with MIPs and play an important role in caring for them 24,13) . Previous studies showed that the level of caregiver burden is related to the severity of illness of the MIPs 25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support a previous study which showed that PHNs utilized multiple sources of data for identifying an individual's health condition 18) . Additionally, in Japan, many families live with MIPs and play an important role in caring for them 24,13) . Previous studies showed that the level of caregiver burden is related to the severity of illness of the MIPs 25) .…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the mental health conditions of MIPs using early warning signs was a key factor in reducing the readmission rate, as well as medicald costs 12) . However, identifying the relapse of patients is difficult because it depends greatly on the level of recognition of the patients and their families living in the community 13) . Furthermore, relapse causes problematic behaviors in MIPs.…”
mentioning
confidence: 99%
“…Kayama and colleagues evaluated the effectiveness of the nationwide Japanese Outreach Model Project (JOMP), established in 2011 by the Japanese Ministry of Health to provide multidisciplinary outreach services for eligible patients to prevent them from repeated hospitalisations 2. Patients, who do not or will not use regular Japanese outpatient care funded by public insurance, but are at high-risk for hospitalisations are the target population of JOMP.…”
Section: Methods Of the Studymentioning
confidence: 99%
“…Kayama et al [3] explained that, as a reaching out approach, in Japan, it is the intervention in family and the prevention against worsening physical symptom that caused the reduction of re-hospitalization. According to a study by Nakanishi et al [11], nurses' involvement in patients in making the plan of discharge since the acute care period caused the decline of the rate of re-hospitalization.…”
Section: Assessment Items Priority In the Acumentioning
confidence: 99%
“…Long-term hospitalization is a problem in psychiatric hospitals in Japan [1]. Today, the Japanese government is promoting outreach services [2], and patient transitions from hospital to community as social rehabilitation strategy [3]. This situation is essential to prevent re-admissions and early discharge of patients, and to provide appropriate treatments and interdisciplinary care to patients with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%